2014
DOI: 10.1016/j.jue.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Land use regulations and the value of land and housing: An intra-metropolitan analysis

Abstract: a b s t r a c tInferences about the determinants of land prices in urban areas are typically based on housing transactions, which combine payments for land and long-lived improvements. In contrast, we investigate directly the determinants of urban land prices within a metropolitan area -the San Francisco Bay Area. Our analysis focuses on the relationship between the regulation of urban development within different jurisdictions and land prices, while considering other factors that shape the value of land, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(93 citation statements)
references
References 40 publications
1
73
0
8
Order By: Relevance
“…Recent work on similar topics features significantly more advanced methods such as the combining of spatial methods with hedonic housing data (Bin et al 2011) or with dynamic models (Husby et al 2014). While not featuring elevation as a primary investigative target, Kok, Monkkonen, and Quigley (2014) find evidence of elevation effects in San Francisco land value. Although only tangentially related to elevation effects as discussed in this paper, these analyses are nonetheless relevant in suggesting the possibility that elevation may influence urban gradients such as rent and density.…”
Section: Prior Literaturementioning
confidence: 99%
“…Recent work on similar topics features significantly more advanced methods such as the combining of spatial methods with hedonic housing data (Bin et al 2011) or with dynamic models (Husby et al 2014). While not featuring elevation as a primary investigative target, Kok, Monkkonen, and Quigley (2014) find evidence of elevation effects in San Francisco land value. Although only tangentially related to elevation effects as discussed in this paper, these analyses are nonetheless relevant in suggesting the possibility that elevation may influence urban gradients such as rent and density.…”
Section: Prior Literaturementioning
confidence: 99%
“…There is abundant evidence that land development restrictions increase house prices (Glaeser et al, 2006;Kok et al, 2014), and can impose limitations on employment growth (Hsieh and Moretti, 2017). This implies that restrictions are relevant and that restrictions on land use in the vicinity of large cities induce people to reside further away.…”
Section: Introductionmentioning
confidence: 99%
“…www.eea.europa.eu/data-and-maps/indicators/nationally-designated-protectedareas#tab-latest-figures-and-vizualizations. 4 Environment Canada -Canadian Protected Areas -Status Report 2006-2011 It has been shown that land-use regulations have strong influence on the supply of housing, and thus its price (Pollakowski and Wachter, 1990;Sommerville, 2000a and2000b;Raphael, 2004 andGlaeser and Ward, 2009;Kok et al, 2014), its location and pattern of development (Quigley and Swoboda, 2007;Ihlanfeldt, 2007;Cheshire and Vermeulen, 2009), the timing of development (Mayer and Sommerville, 2000a;Cunningham, 2007), and social segregation (Levine, 1999). Land-use regulations may also potentially have non-negligible distributional effects (Quigley and Swoboda, 2007;Cheshire and Vermeulen, 2009).…”
Section: Introductionmentioning
confidence: 99%